Pengaruh Kontribusi Dana Peserta terhadap Nilai Surplus Underwriting Pada Pt. Asuransi Jiwa Syari’ah Al Amin Bandar Lampung - dwi cahyani, miranti (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2022)
Participant contribution (premium) is a form of mutual cooperation in which each participant contributes funds to PT. Al Amin Syari'ah Life Insurance and these participants are entitled to compensation for their contribution based on the amount of shares (premium) owned (paid). In the context of Sharia, financial investment can be understood as engaging in trade or business endeavors. These business activities encompass various forms, including enterprises focused on products, assets, or services. This research is a study conducted using a combined approach of quantitative and qualitative methods. The application of the analytical method in this study is to use a combination of quantitative and qualitative. Based on the correlation coefficient test, the results stated that the participant fund contribution variable (X) had a moderate effect on the underwriting surplus value variable (Y). From the hypothesis test with consideration of the decision to compare the tcount value with the ttable value, the results state that H0 is accepted and H1 is rejected. Based on the determination test, the results stated that the variable contribution of participants' funds (X) only affected the underwriting surplus value variable (Y) of 23.6%. It can be concluded from the study's findings that the hypothesis proposed has been invalidated, as no significant impact was observed between the contribution of participant funds and the underwriting surplus value at PT. Al Amin Sharia Life Insurance in Bandar Lampung.